Legal approach on assessment of contractors' entitlement to extension of time - Chong, Heap Yih; Leong, Y. (Academic Journals, 2012)
Delay is acknowledged as the most common, costly, complex and risky problem encountered inconstruction projects. Different project scheduling and planning techniques would have differentapproaches of assessment of extension of time (EOT). Hence, this research aims to (a) review the legalpositions in Malaysia with regards to EOT assessment and (b) evaluate the contractors ‘entitlement toEOT from case studies in Malaysia. Literature study was carried out for the first objective whereas tworeal-case studies on different delay analysis methods were investigated later. Subsequently, three legalexperts of construction claims were interviewed. The literature showed that the courts and arbitrationtribunals have not generally gone into great depths for EOT assessment and delay analysis. Theexperts, considering the second objective, delivered a unanimous opinion that both cases were weak interms of the entitlement for EOT due to the issue of concurrency of the delaying events and the lack ofaccuracy of the work programme.